2000
DOI: 10.1073/pnas.97.26.14656
|View full text |Cite
|
Sign up to set email alerts
|

Active segregation by the Bacillus subtilis partitioning system in Escherichia coli

Abstract: Bacterial genes required for proper partitioning consist of two transacting genes that encode proteins and a cis-acting gene that functions like a centromere. Plasmids actively partitioning by means of these genes migrate from midcell to the cell quarters and are tethered to these sites until the cells divide. Previously the partitioning genes were mainly found on plasmids and phages in Escherichia coli. However, progress in genome sequencing reveals that partitioning genes are ubiquitous in many bacterial pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
161
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(172 citation statements)
references
References 36 publications
10
161
0
1
Order By: Relevance
“…Research has shown that 8 of the 10 sequences are bound by Spo0J in vivo, and that the presence of one such site on an otherwise unstable plasmid stabilizes the plasmid in a Soj-and Spo0J-dependent manner, demonstrating that the site, parS, can function as a partitioning site (Lin & Grossman 1998). Moreover, it has since been shown that both the B. subtilis and P. aeruginosa partitioning machineries can function in E. coli (Godfrin-Estevenon et al 2002;Yamaichi & Niki 2000).…”
Section: Par Proteins Encoded By Bacterial Chromosomes-components Of mentioning
confidence: 99%
See 4 more Smart Citations
“…Research has shown that 8 of the 10 sequences are bound by Spo0J in vivo, and that the presence of one such site on an otherwise unstable plasmid stabilizes the plasmid in a Soj-and Spo0J-dependent manner, demonstrating that the site, parS, can function as a partitioning site (Lin & Grossman 1998). Moreover, it has since been shown that both the B. subtilis and P. aeruginosa partitioning machineries can function in E. coli (Godfrin-Estevenon et al 2002;Yamaichi & Niki 2000).…”
Section: Par Proteins Encoded By Bacterial Chromosomes-components Of mentioning
confidence: 99%
“…Importantly, the chromosomal partitioning proteins can be engineered to function in the same way as plasmid par proteins to stabilize an otherwise unstable replicon and direct its correct positioning within the cell (Godfrin-Estevenon et al 2002;Lin & Grossman 1998;Yamaichi & Niki 2000). Furthermore, null mutants of ParB are lethal in Caulobacter crescentus (Mohl et al 2001), and mutations in spo0J in B. subtilis result in the formation of up to 3% anucleate cells (Ireton et al 1994).…”
Section: Par Proteins Encoded By Bacterial Chromosomes-components Of mentioning
confidence: 99%
See 3 more Smart Citations